Multiyear dual nitrate isotope signatures suggest that N‐saturated subtropical forested catchments can act as robust N sinks. (21st May 2016) - Yu, Longfei; Zhu, Jing; Mulder, Jan; Dörsch, Peter
Abstract: In forests of the humid subtropics of China, chronically elevated nitrogen (N) deposition, predominantly as ammonium (NH4 + ), causes significant nitrate (NO3 − ) leaching from well‐drained acid forest soils on hill slopes (HS), whereas significant retention of NO3 − occurs in near‐stream environments (groundwater discharge zones, GDZ). To aid our understanding of N transformations on the catchment level, we studied spatial and temporal variabilities of concentration and natural abundance (δ 15 N and δ 18 O) of nitrate (NO3 − ) in soil pore water along a hydrological continuum in the N‐saturated Tieshanping (TSP) catchment, southwest China. Our data show that effective removal of atmogenic NH4 + and production of NO3 − in soils on HS were associated with a significant decrease in δ 15 N‐NO3 −, suggesting efficient nitrification despite low soil pH. The concentration of NO3 − declined sharply along the hydrological flow path in the GDZ. This decline was associated with a significant increase in both δ 15 N and δ 18 O of residual NO3 −, providing evidence that the GDZ acts as an N sink due to denitrification. The observed apparent 15 N enrichment factor ( ε ) of NO3 − of about −5‰ in the GDZ is similar to values previously reported for efficient denitrification in riparian and groundwater systems. Episode studies in the summers of 2009, 2010 and 2013 revealed that the spatial pattern of δ 15 N and δ 18 O‐NO3 − in soil water was remarkably similar from year to year. The importance of denitrification as a major N sink was also seen at the catchment scale, as largest δ 15 N‐NO3 − values in stream water were observed at lowest discharge, confirming the importance of the relatively small GDZ for N removal under base flow conditions. This study, explicitly recognizing hydrologically connected landscape elements, reveals an overlooked but robust N sink in N‐saturated, subtropical forests with important implications for regional N budgets.